PERFORMANCE ANALYSIS OF THE THERMOELECTRIC TEC 12706-BASED COOLING SYSTEM IN COOLER BOX DESIGN - Abdul Muchlis; Kurnia Yogo Utomo; Supriyono; Tri Mulyanto (International Journal Science and Technology, 2023)
The most widely used refrigeration machine today is a refrigeration machine that operates with a vapor compression cycle (SKU). To operate a vapor compression machine, refrigerant is needed as a working fluid. The most widely used refrigerants are chlorofluorocarbon (CFC) and hydrochlorofluorocarbon (HCFC) refrigerants. However, their use can damage the ozone layer and has a great potential to increase the effects of global warming. Therefore, a refrigeration system that is environmentally friendly and also has low power is needed, this can be fulfilled by using thermoelectric. This research was conducted to analyze the performance of temperature differences, heat absorbed, cooling capacity and COP in thermoelectric-based cooler boxes, thermoelectric performance with variations in input voltage and with variations in the addition of heatsinks where the method used is experimental by controlling the variable input voltage. From the research results, the calorific value absorbed is proportional to the increase in the applied voltage. Where the greater the voltage applied, the heat absorbed will be higher and the input power that enters the thermoelectric module is directly proportional to the incoming voltage where the greater the voltage. Then the power that goes into the thermoelectric will also be even greater. Whereas the COP value will decrease as the voltage increases and the best thermoelectric performance is with a voltage of 10 V. This can be seen after 60 minutes, the temperature difference value is 6.6 0K, the absorbed calorific value is 19,150 W, and the COP is 0.921. The thermoelectric performance is not only based on the COP value but also based on a review of the electric power consumed and the cooling speed during the 60 minute test. Then for the addition of a copper heatsink the COP value is 0.4832 and the temperature drop in the cooler box is only 3.9 0K, the value is lower than without the additional heatsink due to the gap between the aluminum heatsinks.